Experimental autoimmune encephalomyelitis and age-related correlations of NADPH oxidase, MMP-9, and cell adhesion molecules: The increased disease severity and blood-brain barrier permeability in middle-aged mice - Seo, Ji-Eun; Hasan, Mahbub; Han, Joon-Seung; Kang, Min-Jung; Jung, Byung-Hwa; Kwok, Seung-Ki; Kim, Ho-Youn; Kwon, Oh-Seung (ELSEVIER SCIENCE BV, 2015)
The aim of the present study was to investigate effect of two different ages (6 weeks [6 W] vs. 6 months [6 M]) on blood-brain barrier (BBB) disruption in EAE and evaluate the expression and correlations of NADPH oxidase, MMP-9, ICAM-1, and VCAM-1 following increased age and EAE induction. Higher disease severity was observed in 6 M-EAE than 6 W-EAE. The four factors were significantly elevated and correlated in 6 M-EAE. BBB permeability increased with statistically significant interaction between age and EAE effects. We suggest strong correlations between NADPH oxidase and the other factors play important roles in increased BBB disruption and EAE susceptibility in middle-aged mice. (C) 2015 Elsevier B.V. All rights reserved.